Management of spent shea waste: An instrumental characterization and valorization in clay bricks construction. (June 2017) - Adazabra, A.N.; Viruthagiri, G.; Shanmugam, N.
Graphical abstract: Highlights: The shea agroindustry, is commonly targeted for various developmental needs. Challenges of spent shea waste effective management briefly outlined. Inert and fuel-containing nature of shea waste found suitable for use in construction. Over 95 wt% weight loss of spent shea waste shows it is an excellent porosifier. Abstract: This work studies the reuse of spent shea waste as an economic construction material in improving fired clay bricks manufacture aside providing a novel approach to ecofriendly managing its excessive generated from the shea agroindustry. For this purpose, the influence of spent shea waste addition on the chemical, mineralogical, molecular bonding and technological properties (i.e. compressive strength and water absorption) of the fired clay bricks were extensively investigated. The results indicated that the chemical, mineralogical, phase transformations, molecular bonding and thermal behavior of the produced bricks were practically unaffected by the addition of spent shea waste. However, spent shea waste addition increased the compressive strengths and water absorptions of the brick products. Potential performance benefits of reusing spent shea waste was improved fluxing agents, energy-contribution reaction, excellent porosifying effect, reduced thermal conductivity and enhanced compressive strengths of the brick products. This research has therefore provided compelling evidence that could create newfound route for the synergistic ecofriendly reuse of spent shea waste to enhance clay brick construction aside being a potential mainstream disposal option.